DNMT aberration-incurred GPX4 suppression prompts osteoblast ferroptosis and osteoporosis - Binjia Ruan; Jian Dong; Fanhao Wei; Zhiqiang Huang; Bin Yang; Lijun Zhang; Chuling Li; Hui Dong; Wangsen Cao; Hongwei Wang; Yongxiang Wang (Bone Research, 2024)
Abstract Osteoporosis (OP) is a common and fracture-prone skeletal disease characterized by deteriorated trabecular microstructure and pathologically involving various forms of regulated bone cell death. However, the exact role, cellular nature and regulatory mechanisms of ferroptosis in OP are not fully understood. Here, we reported that OP femurs from ovariectomized (Ovx) mice exhibited pronounced iron deposition, ferroptosis, and transcriptional suppression of a key anti-ferroptotic factor GPX4 (glutathione peroxidase 4). GPX4 suppression was accompanied by hypermethylation of the Gpx4 promoter and an increase in DNA methyltransferases DNMT1/3a/3b and was transcriptionally promoted by repressive KLF5 and the transcriptional corepressors NCoR and SnoN. Conversely, DNMT inhibition with SGI-1027 reversed promoter hypermethylation, GPX4 suppression and ferroptotic osteoporosis. In cultured primary bone cells, ferric ammonium citrate (FAC) mimicking iron loading similarly induced GPX4 suppression and ferroptosis in osteoblasts but not in osteoclasts, which were rescued by siRNA-mediated individual knockdown of DNMT 1/3a/3b. Intriguingly, SGI-1027 alleviated the ferroptotic changes caused by FAC, but not by a GPX4 inactivator RSL3. More importantly, we generated a strain of osteoblast-specific Gpx4 haplo-deficient mice Gpx4 Ob+/− that developed spontaneous and more severe ferroptotic OP alterations after Ovx operation, and showed that GPX4 inactivation by RSL3 or semi-knockout in osteoblasts largely abolished the anti-ferroptotic and osteoprotective effects of SGI-1027. Taken together, our data suggest that GPX4 epigenetic suppression caused by DNMT aberration and the resulting osteoblastic ferroptosis contribute significantly to OP pathogenesis, and that the strategies preserving GPX4 by DNMT intervention are potentially effective to treat OP and related bone disorders.